Training of Integrated Family and Anti-Drug Ambassador for Mothers of Bhayangkari Ranting Manggala - Asmah; A. Melantik Rompegading; Fentry Hernaningsi Ruing (Law Doctoral Community Service Journal, 2023)
Bhayangkari is an organization of police wives where all members who are members of it have various roles not only as wives but also as role models for their families and their environment. Therefore, the participation of Bhayangkari mothers apart from supporting their husbandâ€™s activities and career as a police officer, is also required to always develop their knowledge, and one of them is knowledge about the importance of an integrated family and the importance of understanding the dangers of drugs that are currently rife among children. -children and youth. The main problem in this PKM is the high number of cases of drug abuse among teenagers in the jurisdiction of the Manggala Police, Makassar City, South Sulawesi. Based on data obtained from Basic Education Data of the Directorate General of Early Childhood Education, Basic Education and Secondary Education of the Ministry of Education and Culture, in the Manggala sub-district there are 42 Elementary Schools, 20 Junior High Schools, 13 Senior High Schools, 7 Vocational High Schools, and 3 SLB.[1] The busyness and lack of understanding and supervision of parents at home, the busyness of teachers in schools providing materials related to the education curriculum, and the limited cadres of BNN South Sulawesi Province as narcotics extension agents, has encouraged the determination of the proposing team to activate Bhayangkari Ranting Manggala women to participate active as new anti-drug ambassadors who will be scattered in various schools in Manggala District to save young people from an early age. The solution offered is to provide training for Bhayangkari Ranting Manggala mothers by bringing in experts and resource persons not only in the field of narcotics but also psychiatrists who understand growth and development as well as problems and special approaches for children and adolescents. The Makassar Police Narcotics Research Unit and representatives of the South Sulawesi Province National Narcotics Agency (BNN) will also actively participate by providing outreach or counseling on P4GN (Prevention of Eradication of Drug Abuse and Circulation). The target achievements of this PKM activity are: 1) Bhayangkari members of the Manggala branch are ready to go directly to become integrated family ambassadors and anti-drug ambassadors to schools in the Manggala sub-district, at recitations, at mosque youth, and church youth, and in various youth organizations which is in the Manggala sub-district environment. The motto of this activity is: â€œIf not us, then who will? If not now when?â€ 2) The existence of an annual Work Program of the Manggala Polsek related to anti-narcotics counseling, and 3) the election of Manggala as an integrated and anti-drug family driving sub-district by the government and authorized agencies. 4) Reducing the number of cases of drug abuse in the jurisdiction of the Manggala Police. [1] Data Pokok Pendidikan Direktorat Jenderal Pendidikan Anak Usia Dini, Pendidikan Dasar dan Pendidikan Menengah Kementerian Pendidikan dan Kebudayaan https://dapo.dikdasmen.kemdikbud.go.id/sp/3/196014,